A seven-year study of large mammal populations in the Sahel, West Africa - Hema, E.M.; Belemsobgo, U.; Ouattara, Y.; Tou, I.M.; Sanou, Y.; Karama, M.; Fa, J.E.; Luiselli, L. (Elsevier, 2023)
The dry savannahs of the Sahelian vegetation zone house a remarkable community of large mammals that have been less studied than their counterparts in the eastern Africa. Here we examine some aspects of the ecology of a community of twenty different large mammal species in a savannah of Burkina Faso, for a relatively long-term period (seven years). We observed remarkable interannual differences in terms of (i) number of contacts and (ii) their groups size (range of groups). Nonetheless, the calculated Kilometric Index of Abundance, with all species pooled, showed a relatively stable value of 0.88–1 individual per Km, apart in 2012 when it decreased to 0.7. GLM models on the observed number of contacts and group sizes revealed that there were significant effects of the species, but neither of the year nor of the season. Remarkable species-specific density fluctuations throughout time were observed when applying the DISTANCE methodology to the dataset. The sex ratio showed great fluctuations between the years and by species, even if there was a general predominance of females.